2020
DOI: 10.1093/braincomms/fcaa044
|View full text |Cite
|
Sign up to set email alerts
|

Altered cerebrovascular response to acute exercise in patients with Huntington’s disease

Abstract: The objective of this study was to determine whether a single session of exercise was sufficient to induce cerebral adaptations in individuals with Huntington’s disease and to explore the time dynamics of any acute cerebrovascular response. In this case–control study, we employed arterial-spin labelling MRI in 19 Huntington’s disease gene-positive participants (32–65 years, 13 males) and 19 controls (29–63 years, 10 males) matched for age, gender, body mass index and self-reported activity levels, to measure g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…Hartmann and colleagues (2020) found that non-smokers exhibited a larger increase in gCBF during exercise compared to smokers. Finally, Steventon and colleagues (2020) reported that participants who carry a positive gene for Huntington’s Disease showed a significant increase in rCBF, while controls did not. Besides health, fitness may play an essential role in the effects of acute exercise on CBF (Braz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartmann and colleagues (2020) found that non-smokers exhibited a larger increase in gCBF during exercise compared to smokers. Finally, Steventon and colleagues (2020) reported that participants who carry a positive gene for Huntington’s Disease showed a significant increase in rCBF, while controls did not. Besides health, fitness may play an essential role in the effects of acute exercise on CBF (Braz et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the specific CBF measurement technique used, most studies reported an increase in global CBF during exercise (Hartmann et al, 2020;Hiura et al, 2009;Hiura et al, 2018;Perdomo et al, 2019;Smith et al, 2014;Tari et al, 2021). Regional cerebral blood flow (rCBF), on the other hand, may increase during (Hiura et al, 2013;Hiura et al, 2018;Lyngeraa et al, 2013;Robertson et al, 2015;Steventon et al, 2019;Steventon et al, 2020) or decrease (Hiura et al, 2018;MacIntosh et al, 2017;Pontifex et al, 2018;Robertson et al, 2015;Robertson et al, 2015) after a single bout of exercise. Specifically, Hiura and colleagues (2018) reported a significant increase in cerebral blood flow in the following areas: et al, 2010;Imray et al, 2005;Matsukawa et al, 2015;Neary et al, 2008;Pugh et al, 2015;Santos-Concejero et al, 2017;Sato et al, 2011;Shibuya et al, 2004;Tallon et al, 2019;Tsubaki et al, 2016).…”
Section: Cerebral Blood Flow Measurement Characteristicsmentioning
confidence: 99%
“…Increases in vessel density, BBB permeability and VEGF-A release were observed in HD patients and animal models of HD (Steventon et al, 2020). There is evidence that BBB leakage increases alongside disease progression (Drouin-Ouellet et al, 2015).…”
Section: Altered Blood-brain Barrier and Angiogenesis In Huntington's Diseasementioning
confidence: 99%
“…During problem-solving activities, such as solving a maze or resting their eyes open while looking at a modified maze, patients with HD showed increased CBF in the caudate nucleus (Deckel and Duffy, 2000;. Following physical activity, HD patients were associated with CBF hyperperfusion compared to the control group (Steventon et al, 2020).…”
Section: Vascular Links To Huntington's Diseasementioning
confidence: 99%
“…We have had a lot of success so far in Volume 2 and published fascinating papers. To name but a few, we have published work demonstrating that exercise exposes latent Huntington’s disease pathology ( Steventon et al , 2020 ), a study linking Alzheimer’s risk gene BIN1 to synaptic tau accumulation ( Glennon et al , 2020 ), our first field potential article describing translational neuroscience from a PhD student perspective ( Davies et al , 2020 ), and a review on nodding syndrome, an epileptic disorder that occurs in clusters in sub-Saharan Africa ( Olum et al , 2020 ). We have also been working closely with our sister journal Brain and now have a shared YouTube channel for video abstracts https://www.youtube.com/channel/UClJJHH2xKQk8uZTC7-mJICg .…”
mentioning
confidence: 99%